Gender visibility and erasure - Segal, Marcia Texler, 1940-; Demos, Vasilikie P. (Advances in gender research ;, 2022)
Gender can be rendered invisible when the gendered nature of institutions is ignored or when the genders of participants in events or movements are not identified. The genders of non-binary and gender-diverse individuals can be erased when gender is conceived of as binary. From an intersectional perspective, genders of people of various classes, castes, races, ethnicities, ages, occupations, or other specific characteristics may be absent from data, erased from public view or rendered invisible by stereotypes or policy decisions. Gender Visibility and Erasure offers a unique way of focusing on gender by identifying the multiple contexts in which issues of visibility, invisibility, and erasure manifest. It is a consideration of who is seen and who is ignored, who has voice and who is silenced, who has agency and who is controlled. Social, cultural, and political factors associated with gender and visibility are also discussed throughout the work. International in perspective, further considerations are made around how gender visibility may change over time in varying contexts such as migration, a program for recruiting lower income girls into STEM fields, academia, government family planning policy, and domestic violence. This 33rd volume of the Advanced Gender Research series, Gender Visibility and Erasure is the ideal work for those studying and researching the in/visibility aspects regarding gender and how this currently and may continue to impact society.